Lire deux carnets de voyage du xxe siècle : Michel Vieuchange et Raymond Maufrais - Gilles Louÿs (Viatica)
This article examines the commonalities that unite the notebooks of two young travellers, each of whom died in a raid during an extreme journey in the 20th century: Michel Vieuchange and Raymond Maufrais. Paradoxically, these travel journals and diaries were not meant to be read, yet have been of great editorial success, which can no doubt be explained by the tragic story associated with them. The author seeks to resolve the question of the addressee or addressees of these journals and questions the ways in which they should be read, be they literary or otherwise.